Pengaruh perceived risk, perceived benefit dan brand image terhadap brand loyalty melalui strategic brand communication sebagai variabel moderasi - Joko Wiyono (FADZAT: Jurnal Ekonomi Syariah, 2021)
The purpose of this study is to analyze: 1) the effect of perceived risk on strategic brand communication. 2) the effect of perceived benefits on strategic brand communication. 3) the influence of brand image on strategic brand communication. 4) the effect of perceived risk on brand loyalty. 5) the effect of perceived benefits on brand loyalty. 6) the influence of brand image on brand loyalty. 7) the influence of strategic brand communication on brand loyalty. 8) indirect effect of perceived risk on brand loyalty through strategic brand communication. 9) indirect effect of perceived benefit on brand loyalty through strategic brand communication. 10) the indirect effect of brand image on brand loyalty through strategic brand communication. The number of subjects for M2M Indonesian Fast Food Gondang Mojokerto customers is 4741 customers/consumers. In sampling, the sample size is determined by the Slovin formula with a significance level of 0.01 so that the sample is determined to be 98 customers/consumers. In this research, the writer uses multiple linear regression analysis technique with SPSS program. V. 26.0. From the results of the analysis and discussion, it is concluded as follows: 1) perceived risk has no effect on strategic brand communication; 2) perceived benefit has a significant effect on strategic brand communication; 3) brand image has a significant effect on strategic brand communication; 4) perceived risk has a significant effect on brand loyalty; 5) perceived benefit has a significant effect on brand loyalty; 6) brand image has no effect on brand loyalty; 7) strategic brand communication has a significant effect on brand loyalty; 8) perceived risk has an indirect effect on brand loyalty through strategic brand communication as a moderating variable; 9) perceived benefit has an indirect effect on brand loyalty through strategic brand communication as a moderating variable; 10) brand image has an indirect effect on brand loyalty through strategic brand communication as a moderating variable.